Exploring Jungian Archetypes in Abuela Alma Madrigal’s Behaviour in Disney’s Encanto - Widiena Aurellia Saifani; Sang Ayu Isnu Maharani; Putu Wahyu Widiatmika (Systematic Literature Review Journal, 2026)
This study analyzes how Abuela Alma Madrigal's behaviors toward her family in Disney's Encanto (2021) are influenced by Jungian archetypes. The psychological analysis of matriarchal characters in animated films has received little attention, despite the widespread usage of Jungian theory in film analysis. The aim of this study is to identify the Jungian archetypes that Abuela embodies and analyze how they influence her relationships with the Madrigal family. Data was gathered by repeatedly watching the movie using a qualitative, descriptive approach. Jung's archetypal theory (1959) served as the main framework for the analysis of a selection of dialogues that were transcribed and classified based on specific archetypes. The results show that Abuela's behavior is greatly influenced by five archetypes. She is motivated by the persona archetype to maintain a public persona of magical perfection, valuing each family member according to how they contribute to this image. The trauma of losing her husband Pedro is the source of the Shadow archetype, which takes the form of denial and blame projection until Mirabel confronts it. The Great Mother archetype illustrates how her parental love turned into conditional acceptance and overprotection. The Wise Old Woman archetype highlights the difference between her appearance of authority and the personal doubt she carries. Finally, the Self archetype signifies her psychological transformation as she completely accepts the value of each family member and integrates her suppressed fears, completing Jung's individuation process. These results validate that Jungian theory provides a useful framework for analyzing matriarchal characters in animated films and show how universal psychological patterns associated with trauma, authority, and family dynamics can be meaningfully reflected in modern animated films.